(untitled) - Wheelen, Thomas L. (Upper Saddle River, NJ, 2008)
This comprehensive book offers an engaging look into new and traditional strategic management topics. Its thorough coverage helps readers develop an understanding of the wide range of theories and research available in this field—from competitive strategy and industry analysis to environmental trends and ethics. Integration of international issues throughout provides an essential understanding of global economics and its impact on business activities in any location. This book contains the latest research and examples of well-known and not-so-well known companies dealing with complicated strategic issues. . For directors of strategic planning, competitive intelligence analysts, and strategic planners (editorial review)
Keywords: Strategic management,Strategic planning,Hoạch định chiến lược